Uneven diffusion: a multi-scale analysis of rural settlement evolution and its driving forces in China from 2000–2020 - Yingxue Rao; Chenxi Wu; Qingsong He (Humanities & Social Sciences Communications)
Abstract In recent years, the spatial and temporal patterns of rural settlement expansion in China have shifted significantly due to rapid urbanization and industrialization. This study examines rural settlement expansion in China from 2000 to 2020, using the Landscape Expansion Index (LEI) and GIS spatial analysis to assess changes in land use scale and related factors. The findings reveal that: (1) From 2000 to 2020, China saw a rapid and large-scale expansion of rural settlements, with the total area increasing by 40,322.74 km², 87.42% of which resulted from outlying expansion, indicating a clear diffusion trend. (2) The movement of rural settlements has predominantly followed a southeast–northwest axis, focusing on the middle reaches of the Yangtze River, with a clockwise rotation shift. (3) Settlement expansion has been primarily concentrated in low-elevation, waterfront, and road-adjacent areas, where GDP per capita and population density significantly influence settlement patterns. These results offer valuable insights for optimizing the spatial distribution and industrial restructuring of rural settlements, as well as for guiding rural spatial planning and industrial policy development.